Exchange anisotropy in the skyrmion host GaV4S8. (21st December 2016) - Ehlers, D; Stasinopoulos, I; Kézsmárki, I; Fehér, T; Tsurkan, V; von Nidda, H-A Krug; Grundler, D; Loidl, A
Abstract: Using ferromagnetic resonance spectroscopy at 34 GHz we explored the magnetic anisotropy of single-crystalline GaV4 S8 in the field-polarized magnetic state. We describe the data in terms of an easy-axis type uniaxial anisotropy with an anisotropy constant K 1 = 1.6 ⋅ 10 5 erg cm −3 at 2 K, corresponding to a relative exchange anisotropy Δ J / J ≈ 5 %, and about 1.0 ⋅ 10 5   erg cm −3 near 11 K, i.e. at temperatures where the skyrmion-lattice phase was recently discovered. The relatively large value of K 1 explains the confinement of the skyrmion tubes to the ⟨ 1   1   1 ⟩ easy axes. A distinct set of resonances in the spectra is attributed to the co-existence of different rhombohedral domains. Complementary broadband spectroscopy demonstrates that non-collinear spin states may sensitively be detected by electron spin resonance techniques.